A Nanoscale Hot-Wire Flow Sensor Based on CMOS-MEMS Technology - Wang, Xiaoyi; Fang, Zetao; Song, Xiangyu; Xu, Wei (Frontiers in Mechanical Engineering, 2022)
In this paper, we proposed an ultrafast and nanoscale hot-wire flow (NHF) sensor implemented in a 0.18 µm complementary metal-oxide-semiconductor microelectromechanical system (CMOS-MEMS) technology. The nanoscale wire was released and reduced in thickness and width by an in-house developed post-CMOS fabrication process, hence the heat conduction loss is greatly suppressed, while the response time of the NHF sensor is significantly improved. Benefiting from the nano size of the hot-wire (a width of 622 nm), the NHF sensor exhibits an ultrafast response time of 30 µs (@ airflow velocity of 0 m/s), a wide flow range of 0–30 m/s, and a cut-off frequency of 21 kHz under the constant temperature (CT) mode. In addition, an equivalent circuit model (ECM) was established in PSPICE to predict the NHF sensor performance, and the theoretical simulation results were in good agreement with the experiment results.